Penerapan Primary Chord dan Secondary Chord dengan Pendekatan Primary Beat pada Mata Kuliah Harmoni Manual - Olan Yogha Pratama; Robby Ferdian (FBS Universitas Negeri Padang, 2022)
This study aims to provide basic knowledge and skills for students in the application of Primary and Secondary Chords by limiting the chord composition roadmap centered on the melody of the song which is in the primary beat position. This research can be used as a reference for students in restructuring the Chord Progression of a song or better known as the Reharmonization of Chord for the beginner stage. This research method uses a qualitative research method with an Art Practice-Based Research approach with the object of study in the form of a Kelok Sembilan folk song and a literature study on the theory of the concept of the application of Primary and Secondary Chord harmonies. The results showed that the Primary Beat approach made it easier for students to determine the chord progression arrangement for the song twists, students only needed to follow the strong beats of each bar as a reference for determining the chord progression, so both in theory and practice, students did not have much difficulty playing it. This approach is also very effective to be applied in restructuring the chord progression of other simple songs because it is able to give a newer and fresher feel to the chord progression.